Exploring the Impact of Gender Difference on 3-6 Years Old Children’s Physical Activity Levels (Journal of Education and Development, 2022)
Several studies have shown that children’s physical activity levels (PAL) are not sub-optimal, however, PAL is critical to children’s development. The purpose of this study is to test the hypothesis that whether there is a significant gap between boys and girls on PAL. The gender is ignored in the previous research was remedied in this study. Quantitative methods are employed to collect primary data on PAL in children aged 3-6 years. This study has implications in terms of theory, methodology, and practice, for researchers, practitioners, and parents in the preschool education field.